2017
DOI: 10.1164/rccm.201604-0700oc
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Liposomal Amikacin for Inhalation in Nontuberculous Mycobacterial Lung Disease

Abstract: Although the primary endpoint was not reached, LAI added to a multidrug regimen produced improvements in sputum conversion and 6-minute-walk distance versus placebo with limited systemic toxicity in patients with refractory MAC lung disease. Further research in this area is needed. Clinical trial registered with www.clinicaltrials.gov (NCT01315236).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
165
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 219 publications
(175 citation statements)
references
References 31 publications
6
165
0
4
Order By: Relevance
“…However, this study demonstrated a significant decrease in the positivity of semiquantitative sputum cultures for AFB over the course of treatment with CFZ in both the initial treatment and salvage treatment groups, suggesting that CFZ-containing regimens can help to decrease the mycobacterial burden. Semiquantitative AFB culture positivity is likely to reflect disease burden and was used to assess microbiological responses to the treatment of NTM lung disease in some recently reported studies (38)(39)(40). Given that M. abscessus lung disease is regarded as a chronic, incurable infection and that there are limited antibiotic options, improvement in the health-related quality of life is a reasonable treatment goal, especially in refractory cases (32).…”
Section: Discussionmentioning
confidence: 99%
“…However, this study demonstrated a significant decrease in the positivity of semiquantitative sputum cultures for AFB over the course of treatment with CFZ in both the initial treatment and salvage treatment groups, suggesting that CFZ-containing regimens can help to decrease the mycobacterial burden. Semiquantitative AFB culture positivity is likely to reflect disease burden and was used to assess microbiological responses to the treatment of NTM lung disease in some recently reported studies (38)(39)(40). Given that M. abscessus lung disease is regarded as a chronic, incurable infection and that there are limited antibiotic options, improvement in the health-related quality of life is a reasonable treatment goal, especially in refractory cases (32).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the field of nanomedicine has only scored hits with two oncology drugs. However, pulmonary nanomedicine may soon witness a new dawn because promising nanotechnologies, such as inhaled liposomal amikacin for bronchiectasis, are supported by strong data in late-stage clinical trials (9).…”
Section: Opinions and Ideasmentioning
confidence: 99%
“…Inhaled liposomal amikacin is currently being evaluated in phase II trials for the treatment of nontuberculous mycobacterial infections [45]. The results of an interim analysis were promising, which prompted the data safety monitoring board to recommend continuing the randomized, double-blind, placebo-controlled trial [45].…”
Section: Amikacinmentioning
confidence: 99%